Viability of using wind turbines for electricity generation in electric vehicles - Francisco Rubio; Carlos Llopis-Albert (Multidisciplinary Journal for Education, Social and Technological Sciences)
This paper presents a feasibility study of applying a fluid energy recovery system by means of wind turbines for charging batteries of electric vehicles. This is because the main disadvantage of electric vehicles with regard to conventional fuel automobiles is the scarce capacity of storing sufficient energy to run long distances. This can be carried out by recovering a percentage of the energy used to overcome the aerodynamic drag of the vehicle. This work analysis different case studies, with different driving modes, to quantify the theoretical energy recovered from the vehicle aerodynamics. Results have shown the theoretical possibility to implement this technology in actual electric vehicles.